My Kashmir - "Habibullah, Waj" (Gurgaon, 2014)
Jammu and Kashmir has been ravaged by conflict for sixty years. Caught in a tug-of-war between India and Pakistan, the state is today riven by conflicts of ethnicity, religion and national identity, by friction between national and local governments, and by rival claims to territory. At a moment when abiding peace seems elusive and the nuclearized neighbours are both threatened by terrorism, My Kashmir is a clear-sighted and timely examination of Kashmir's recent history, the bloodshed and betrayals and the urgent quest for a lasting peace.
Keywords: Kashmir- History